(untitled) (Spectrum, 2023)
This study attempts to examine novice students’ writing of essays for English literature, a disciplinary context they have been inadequately exposed to. In order to do that, analysis of English literature essays written by First Year students using Swalesian Move strategy were done to see what structural patterns the essays possessed, what “tactical choices” the students took to express the moves and what was presented in terms of content matter within those moves. This text analysis enabled model development showing the “moves” students are expected to use. The model developed gives insights into the generic structure, that is, Introduction, Body and Conclusion, and content of the essays. The analyses of high and low grade essays explain how some features of writing are more valued than others within the context of the English department, which can eventually help improve students’ writing proficiency. Spectrum, Volume 17, June 2022: 12-30